Epistemology and Hermeneutics of Islamic Religious Education in Madrasahs and Islamic Boarding Schools: Philosophical Reflections on the Integration of Faith, Reason, and Tradition - Uwaisah Uwaisah (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Islamic Religious Education in madrasahs and Islamic boarding schools is a dialectical space between classical scientific traditions and the challenges of modernity. Amid the flow of globalization and the secularization of knowledge, there is a need to reinterpret the epistemological and hermeneutical foundations of Islamic education to remain relevant. The imbalance between normative teaching and practical reality necessitates a philosophical approach that harmoniously integrates faith, reason, and traditional heritage. This study aims to analyze in depth the epistemological structure and hermeneutic approach in PAI implemented in madrasahs and Islamic boarding schools, and to examine how both can strengthen the integration of Islamic values in a contemporary context. The method is a qualitative approach, including literature reviews and semi-structured interviews with educators in madrasahs and Islamic boarding schools with backgrounds in classical and contemporary Islamic thought. The study's results show that the epistemology of Islamic education in both institutions remains predominantly textual-normative. Still, there is a new tendency towards a more reflective, contextual understanding through hermeneutic readings of religious texts. Pesantren tend to be strong in the transmission of tradition, while madrasahs are more open to integrating modern rationality into their curriculum. The contribution of this article is to offer an integrative model between the approaches of faith (revelation), reason (rationality), and tradition (classical heritage), so that it can enrich the discourse of Islamic educational philosophy and open up space for a more dialogical, critical, and sustainable PAI curriculum renewal.